Electroless Silver Plating Reflectors to Boost the Performance of Vertical Light-Emitting Diodes - Qinjin Wang; Jun Ma; Teng Zhan; Liancheng Wang; Enqing Guo; Zhiqiang Liu; Xiaoyan Yi; Junxi Wang; Guohong Wang; Jinmin Li (IEEE Photonics Journal, 2016)
In this paper, we experimentally demonstrated a novel approach known as electroless silver plating (ESP) for the fabrication of Ag-only reflectors on vertical light-emitting diodes (VLEDs). The Ag reflector that was obtained through the ESP approach shows a higher reflectance of 83% and a lower contact resistivity of $6* 10^{-3}\ Ω·\text{cm}^{2}$ with p-GaN, compared with that fabricated through the conventional electron beam (EB) approach, which shows a reflectance of 75% and a contact resistivity of $6.2* 10^{-2}\ Ω·\text{cm}^{2}$ , respectively. Improvements in the light output intensity-current (L-I) and current-voltage (I-V) results in VLEDs, which originated from the high reflectance and low-contact resistivity of the incorporated ESP–Ag reflector. Our result opens up an alternative and promising way to substitute the traditional EB approach for Ag-based reflector fabrication and, thus, is practically meaningful in real device fabrication, such as with VLEDs.